Development of K-BIM e-Submission prototypical system for the openBIM-based building permit framework - Kim, Inhan; Choi, Jungsik; Teo, Evelyn Ai Lin; Sun, Hongwei (Journal of Civil Engineering and Management, 2020)
With the popularization of Building Information Modeling (BIM) technology, increasing numbers of countries are attempting to introduce BIM into their national building permitting processes. There are also many BIM-related research initiatives worldwide. Likewise, the Korean government has joined this trend by improving its existing e-Submission system, SEUMTER, to provide for BIM-based e-submission and automated code compliance checking. Further, the Ministry of Land, Infrastructure, and Transport in Korea has funded the Korea BIM (KBIM) building e-Submission system project. The Industry Foundation Classes (IFC) data model is an openBIM approach that has been designated as an international standard through the International Organization for Standardization. It is not dependent on specific design tools and is suitable for public works applications. Hence, this study performed a comprehensive analysis of and developed a framework for a prototypical system for an e-Submission process based on the IFC data model. Four main modules were developed to perform code checking, submission, pre-checking, and automated rule-making. A real-world project was used to verify the feasibility and effectiveness of the proposed framework. This study could increase the adoption of BIMbased building e-Submission systems by sharing effective and successful processes.